Concepts of social mobility - Gary S. Fields (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper has two purposes. The first is to define clearly different social mobility concepts and components. The second is to embed these concepts and components into a larger context of social mobility research. The core of the paper develops six mobility concepts and their measures as well as six macromobility components and their measures. The next section relates these concepts and components to issues in the mobility literature. The paper concludes with a checklist of suggestions for conducting and presenting social mobility research: being explicit about several preliminaries-outcome of interest, context, and level of analysis-and then four steps-question, mobility concept(s), mobility measure(s), and empirical findings.
Keywords: D3; D6; J3; J6; 330; Soziale Mobilität; Social mobility; Stand der Forschung; State of research